Neuronal Activity Stimulated by Liquid Substrates Injection at Zusanli (ST36) Acupoint: The Possible Mechanism of Aquapuncture. (6th March 2014) - Chen, Chun-Yen; Lin, Chao-Nan; Chern, Rey-Shyong; Tsai, Yu-Chuan; Chang, Yung-Hsien; Chien, Chi-Hsien
Abstract : Aquapuncture is a modified acupuncture technique and it is generally accepted that it has a greater therapeutic effect than acupuncture because of the combination of the acupoint stimulation and the pharmacological effect of the drugs. However, to date, the mechanisms underlying the effects of aquapuncture remain unclear. We hypothesized that both the change in the local spatial configuration and the substrate stimulation of aquapuncture would activate neuronal signaling. Thus, bee venom, normal saline, and vitamins B1 and B12 were injected into a Zusanli (ST36) acupoint as substrate of aquapuncture, whereas a dry needle was inserted into ST36 as a control. After aquapuncture, activated neurons expressing Fos protein were mainly observed in the dorsal horn of the spinal cord in lumbar segments L3–5, with the distribution nearly identical among all groups. However, the bee venom injection induced significantly more Fos-expressing neurons than the other substrates. Based on these data, we suggest that changes in the spatial configuration of the acupoint activate neuronal signaling and that bee venom may further strengthen this neuronal activity. In conclusion, the mechanisms for the effects of aquapuncture appear to be the spatial configuration changes occurring within the acupoint and the ability of injected substrates to stimulate neuronal activity.